Healthy biological activities in legume flours from industrial cooking - Giangrieco, Ivana; Tamburrini, Maurizio; Tuppo, Lisa; Pasquariello, Maria Silvia; Ciardiello, Maria Antonietta (Food bioscience, 2022)
The legume consumption is increasing because this food represents a rich and sustainable source of plant proteins and biological activities considered effective in the prevention of some chronic diseases, including those age-related. With the aim to characterize functional properties of some legume foodstuffs, the total polyphenolic content and the antioxidant, metal chelation and ACE-inhibitory activity contained in the flours from industrial cooking processes of eight legumes were analyzed using specific spectrophotometric assays. Experimental results show that especially flours from cooked lentils and some beans represent a good source of antioxidants. The estimated amount of chelating activity, ranging from 0.97 (tondini bean) to 4.4 (green lentil) micromoles of EDTA equivalents/g of flours, could contribute to the prevention of the accumulation in the body of heavy metals, representing a possible risk factor for respiratory infectious diseases. Some beans showed an ACE-inhibitory activity higher than chickpea and lentils. It was estimated that 125 g of the bean flour with the highest activity contain an ACE-inhibitory activity corresponding to 25 mg of the drug captopril, representing the initial daily dosage recommended for the treatment of moderate high blood pressure. These data could contribute to formulate personalized diets to address the needs of different subjects. [Display omitted]